The Ottoman Empire during the reign of Sultan Selim III (1789-1807) - محمود حسن; علي إبراهيم; علاء الدين جبور (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
This research talks about one of the ottoman sultan who played amajor role in trying to reform and develop the Ottoman state after it was weakened and disintegrated during the period of the weak sultans, and European countries became bolder towards it and reduced its area, and internal disturbances occurred in it in addition to the janissaries domination over the sultans and the general implementation of orders issued to them, and corruption spread throughout it from buying the appropriate and the high cost of aid and the authority of unjust men over important positions in the state, so Sultan selim III when he reached the throne of the Ottoman Empire, its response was weakness and disintegration, which benefited him to work on trying to develop the Ottoman state and return it to what it was in the time of the strong sultans who were sponsoring Europe, and the janissary forces marched under his authority and the victories over the European armies and helped to expand the area of the Ottoman state, so the rise of Sultan selim III by making new reform arrangements in the Ottoman state internally and externally was not an easy matter in a state that had reached an advanced stage from weakness and dissolution, but he faced many difficulties in trying to control and lead the Ottoman Empire.